Implementasi Aplikasi Learning Management System and Student Attendance pada IDN Academy Berbasis Web - Mesra Betty Yel; Dadang Iskandar Mulyana; Fernanda Adhipramana; Ferry Fajar Pratama; Oka Prasetiyo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
The purpose of this service activity is to assist IDN Academy in improving the learning process and student Attendance through the implementation of the Learning Management System (LMS). Application and web-based Attendance system for students. A waterfall research collaboration service methodology is used to perform the stages of system analysis, system design, implementation, testing, and analysis of results. During the service process, a system analysis was performed to determine the needs and requirements of the LMS application and web-based student Attendance system. In addition, we will create a use case diagram that explains the functions of the entire system and design the system. We then ran the implementation phase, distributing questionnaires on a Likert scale of 1 to 5, and testing the application with black box and system quality tests. Test results showed that the LMS application and web-based student Attendance system enabled IDN Academy to manage student learning and Attendance effectively and efficiently. Respondents also agreed on the quality of the system, achieving an average score of 4.2 on the distributed questionnaire. The results of this service are expected to enable IDN Academy to leverage its LMS application and web-based student Attendance system to improve the quality of student learning and Attendance.